2006
DOI: 10.1007/s00464-004-2231-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of different approaches for minimizing hemodynamic changes during pneumoperitoneum

Abstract: Optimizing volume load is effective for minimizing hemodynamic changes during CP in the head-up and in head-down positions. In general, beta(1)-blockers cannot be recommended because they might additionally compromise myocardial contractility and suppress compensatory reaction of the sympathetic nerve system. Vasodilation has not improved hemodynamic parameters during CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Due to the harmful effects of elevated IAP, it is recommended that the lowest IAP possible be used, allowing adequate exposure of the operative field, rather than a standard pressure [17]. To counteract diminished organ perfusion and decreased cardiac function, generous volume loading is recommended [8,17]. To minimize these harmful effects, we used a low IAP (8)(9)(10)(11)(12) for patients with pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the harmful effects of elevated IAP, it is recommended that the lowest IAP possible be used, allowing adequate exposure of the operative field, rather than a standard pressure [17]. To counteract diminished organ perfusion and decreased cardiac function, generous volume loading is recommended [8,17]. To minimize these harmful effects, we used a low IAP (8)(9)(10)(11)(12) for patients with pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous manuscript, we have already shown that an increased ITBV improves hemodynamic function in all body positions during PN [6]. The selective β-blocker esmolol reduced cardiac output and myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Several literature reports based on laboratory and clinical parameters have given controversial results concerning hemodynamic changes as well as endocrine responses during PN [1,2,3]. Treatments with clonidine, β-blockers, sodium nitroprusside and intravenous administration of fluid were tested to eliminate negative hemodynamic effects of PN in various animal studies [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Increasing the intrathoracic blood volume improved hemodynamic function in all body positions with pneumoperitoneum. Fluid management is the most important element for minimizing pneumoperitoneum side efects [54].…”
Section: Complicationsmentioning
confidence: 99%